Exploring the Use of Interactive Media to Enhance Arabic Language Skills Among Islamic Senior High School Students - Novy Maryani; Dadan Nugraha; Kamilah Eka; Sopandi Putri (Gunung Djati Conference Series, 2026)
Arabic language learning in Madrasah Aliyah (MA) faces significant challenges in bridging the gap between theoretical mastery and practical communicative skills. Conventional teaching methods often fail to accommodate the needs of students in the digital era, who require learning experiences that are more responsive and actively engaging. This study aims to explore and analyze the role and effectiveness of using digital interactive media in improving the four Arabic language skills (Istima’, Kalām, Qirā’ah, and Kitābah) among MA students. This research employs a qualitative–descriptive systematic literature study design, synthesizing findings from indexed scientific journals and curricular policy documents, particularly the Decree of the Minister of Religious Affairs (KMA) Number 183 of 2019. The synthesis results indicate that digital interactive media, especially gamification platforms (such as Kahoot! and Quizizz) and interactive multimedia are effective in significantly increasing students’ motivation and participation. Empirically, the implementation of interactive multimedia has been shown to enhance speaking skills (Mahārah Kalām), with reported improvements of up to 8.37% in average scores in related case studies. Further analysis confirms that the integration of digital media supports the achievement of the three mandated competency domains (Attitude, Knowledge, Skills) outlined in KMA 183. Nevertheless, the main challenges identified include infrastructure limitations and the need to improve teachers’ digital competence. The implications of these findings lead to strategic recommendations for MA institutions to strengthen infrastructure and adopt adaptive, AI-based technologies to support the transformation of Arabic language education.